PENGGUNAAN ALAT PERAGA PADA PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS 8 SMP TENTANG GETARAN HARMONIS - Kuspriyono; Widiasih (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This research was motivated by the low scores obtained by grade 8 students of Bintang Mulia Junior High School in Science-Physics subjects about simple harmonic vibrational materials. The influence of teachers who are very dominant and students who are less active causes a lack of student understanding of the subject matter, resulting in 52% of students obtaining scores below KKM 71. This is what encourages learning improvements that emphasize improving teacher performance in using teaching aids and applying the STAD type learning model. Learning improvement aims to increase students' understanding in science learning, especially harmonious vibration material. This research was conducted in grade 8 of Bintang Mulia Junior High School, Bandung city in the first semester of 2022. The method carried out in this study is Classroom Action Research which consists of two cycles of learning improvement. The instruments used in this study were teacher performance reflection sheets and student learning outcomes tests. Data from teacher performance research in applying learning outcomes were also obtained student learning results about harmonic vibrations from cycle I (73.4) and cycle II (91.4). After teachers improve their performance by using the Student Team Achievement Division (STAD) learning model and using teaching aids in the 1st and 2nd cycle learning process, it can be concluded that there is an increase in student learning outcomes. Thus improving teacher performance using the Student Team Achievement Division (STAD) learning model can be applied in other materials and in other schools.